Bottom‐Up Synthesis of Single Crystal Diamond Pyramids Containing Germanium Vacancy Centers. Issue 7 (14th May 2021) - Nonahal, Milad; White, Simon J. U.; Regan, Blake; Li, Chi; Trycz, Aleksandra; Kim, Sejeong; Aharonovich, Igor; Kianinia, Mehran
Abstract: Diamond resonators containing color‐centers are highly sought after for application in quantum technologies. Bottom‐up approaches are promising for the generation of single‐crystal diamond structures with purposely introduced color centers. Here the possibility of using a polycrystalline diamond to grow single‐crystal diamond structures by employing a pattern growth method is demonstrated. For, the possible mechanism of growing a single‐crystal structure with predefined shape and size from a polycrystalline substrate by controlling the growth condition is clarified. Then, by introducing germanium impurities during the growth, localized and enhanced emission from fabricated pyramid shaped single‐crystal diamonds containing germanium vacancy (GeV) color centers is demonstrated. Finally, linewidth of ∼500 MHz at 4 K from a single GeV center in the pyramid shaped diamonds is measured. The method is an important step toward fabrication of 3D structures for integrated diamond photonics. Abstract : This work reports on the bottom‐up growth of diamond pyramids containing the germanium vacancy (GeV) color centers. The germanium vacancy centers are excellent qubits for quantum photonic applications. Through the pyramid growth the GeV centers are incorporated into the diamond and their emission is enhanced. The excellent optical properties are proved using resonant excitation.